AN ACTION RESEARCH ON DEVELOPING FIRST-GRADE STUDENTS' EMOTIONAL LITERACY THROUGH PICTURE BOOKS - Hsiao-Yuan Chu (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study examined the impact of integrating picture books into emotional education on the emotional competence of first-grade students. Using an action research approach, three students from an elementary school in Miaoli County participated in three picture book lessons—The Angry Soup, The Happiest Gift, and My New Grandma. The study examined changes across four dimensions: emotional awareness, expression, understanding, and regulation, based on observation records, worksheets, and reflective notes. Results showed that all students could accurately recognize and express emotions. Hsiao-Yu and Ai-Hsin demonstrated understanding of emotional causes and empathy, while Dan-Tsai required teacher guidance and long-term support. Hsiao-Yu showed self-regulation, and Ai-Hsin managed negative emotions by shifting attention. Overall, picture book-based instruction effectively enhanced students’ emotional awareness and expression, though emotional regulation and empathy require ongoing development.